On the development of inhibitory projection neurons - Simon, Shane Joseph (My University, 2023)
High precision is critical for normal neural circuit function, but that precision is not innate. The location, strength, and number of inputs in a neural circuit are modified in early postnatal development in a process called refinement. The refinement of long-range excitatory projections is well-known, but less is known about the refinement of long-range inhibitory projections. What we do know about inhibitory projection refinement comes from the glycinergic medial nucleus to the trapezoid body to lateral superior olive (MNTB-LSO) projection of the auditory brainstem. During early postnatal life, the MNTB-LSO projection undergoes morphological and physiological refinement. Notably, the MNTB-LSO projection transiently expresses vesicular glutamate transporter 3 (VGLUT3) and synaptotagmin 1 (Syt1), transiently releases glutamate, and undergoes glutamate-dependent refinement. However, it remains uncertain whether glutamate release is specific to the auditory brainstem or could be a more general phenomenon of inhibitory projections. To shed light on this question, I investigated another inhibitory projection of the hindbrain, the GABAergic Purkinje projection of the cerebellum. The Purkinje projection shares key characteristics with the MNTB-LSO projection, including its inhibitory nature, location in the hindbrain, obvious topographic organization, heterogeneity of the target cells, and expression of VGLUT3 transcript and protein. In this thesis, I sought to determine: 1) whether the expression profile of VGLUT3 and Syt1 in the Purkinje projection matches that of the MNTB-LSO projection, and whether the Purkinje projection also releases glutamate, 2) whether the expression profile of synaptic vesicle protein 2 (SV2) isoforms, SV2B and SV2C, matches the expression profile of other synaptic vesicle proteins in the Purkinje and MNTB-LSO projection, and 3) whether the Purkinje projection undergoes postnatal morphological refinement like the MNTB-LSO projection. I found that like the MNTB-LSO projection, the Purkinje projection transiently expresses VGLUT3 and Syt1, releases glutamate in early postnatal life, and may undergo morphological refinement.
Keywords: Purkinje; refinement; inhibition; cerebellum; VGLUT3; neural circuits; axon; development